2002
DOI: 10.1016/s0002-9440(10)64152-1
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Tumor-Draining Lymph Nodes for Phenotypic and Functional Analysis of Dendritic Cells and T Cells

Abstract: Immune responses against tumor antigens will initially occur in the first tumor-draining lymph node, the sentinel node (SN). Because of extensive diagnostic procedures, obtaining a piece of SN to isolate viable immune cells for functional analyses is often impossible. For this reason an alternative method to obtain viable cells from a lymph node (LN) was investigated, ie, scraping LNs with a surgical blade, and compared with dissociation of total LNs. Tumor-draining lymph nodes were retrieved from five oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…All blue nodes and radioactive nodes with an in vivo-or ex vivo-background count ratio of 2:1 or more were removed using gamma probe (ScintiProbe MR 100, Pol.Hi.Technologies, Rome, Italy). For research purposes SLN processing was performed as previously described with minor modifications [23]. Briefly, SLN was bisected crosswise and one cutting surface was scraped 5 times with a scalpel blade by the pathologists.…”
Section: Patients and Human Samplesmentioning
confidence: 99%
“…All blue nodes and radioactive nodes with an in vivo-or ex vivo-background count ratio of 2:1 or more were removed using gamma probe (ScintiProbe MR 100, Pol.Hi.Technologies, Rome, Italy). For research purposes SLN processing was performed as previously described with minor modifications [23]. Briefly, SLN was bisected crosswise and one cutting surface was scraped 5 times with a scalpel blade by the pathologists.…”
Section: Patients and Human Samplesmentioning
confidence: 99%
“…7 In patient 3, 20 months after vaccination, additional skin tests were performed with KLH, CML,CML/DC, and MoDC. T cells (pre and postvaccination) were isolated and expanded from PBMC as described previously, 8 separated into CD4+ and CD8+ T cells by magnetic microbead separation (Miltenyi, Bergisch Gladbach, Germany), and subsequently cocultured for 4 and 7 days respectively, with CML/DC, uncultured CML cells, or KLH loaded on autologous CML/DC. IFN (release was measured by ELISA 24 h after start of culture (CLB, Amsterdam, The Netherlands) and IFN (elispot assays were performed at the end of coculture as described previously.…”
Section: To the Editormentioning
confidence: 99%
“…IFN (release was measured by ELISA 24 h after start of culture (CLB, Amsterdam, The Netherlands) and IFN (elispot assays were performed at the end of coculture as described previously. 8 KLH plasma IgG levels were measured by titration in a routine ELISA assay, as described (coating with 0.5 mg/ml KLH). 9 In vitro-generated CML/DC displayed morphological DC characteristics with a typical veiled appearance and an immature phenotype (CD40+, CD54+, CD80+, CD83À, and CD86+).…”
Section: To the Editormentioning
confidence: 99%
“…Numerous studies showed that GM-CSF and IL-4 could drive monocytes into DCs, and increase the expression of CD83 on DCs (24). Rouard's research indicated that CD83 molecule was not expressed on DCs in early culture but presented when DCs matured (25), when their capacity to activate T cells was most effective (26,27). However the role of CD83 on mature DCs and T cell activation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to induce large quantities of DCs with typical phenotype and function. So the differences in the secretion of cytokines by TDLN cells in response to the various stimuli may be a reflection of the number of DCs in TDLN population (26,27). It was reported that the application of mature rather than immature DCs in patients was more effective in adoptive immunotherapy (26).…”
Section: Discussionmentioning
confidence: 99%